Point-Spread Analysis of γ-Ray/Depth Spectra for Borehole Monitoring Applications - Elisio, Soraia C.; Bala, Aliyu; Bandala, Manuel; Graham, James; Grievson, Alex; Joyce, Malcolm J. (IEEE transactions on nuclear science, 2023)
An approach to the analysis of γ -ray spectra that might arise as depth profiles from the characterization of radioactivity in boreholes is described. A borehole logging probe, "ABACUS," has been designed and constructed, which comprises a cerium bromide detector and a built-in multichannel analyzer (MCA). This has been tested in a bespoke, laboratory-based testbed built to replicate the borehole environment. An established, semiempirical model has been applied to data arising from the cerium bromide scintillation detector to extract the number of counts under the full-energy peak from each of the resulting γ -ray spectra (in this case the 662 keV line from 137Cs) associated with each depth position, which also enables this information to be isolated from other contributions such as background and the Compton continuum. A complementary approach has been adopted to process the asymmetric and non-Gaussian trend that concerns the full-energy peak count as a function of depth in the borehole testbed for a given depth profile when the testbed is subject to the activity provided by a sealed, 137Cs source. This comprises a modified, Moffat point-spread function (PSF). The Moffat function is a continuous probability distribution based on the Lorentzian distribution. Its particular importance is due to its ability to reconstruct PSFs that comprise wings that cannot be reproduced accurately by either a Gaussian or Lorentzian function. This application of the Moffat formalism to radioactive contamination assessment profiles enables an effective and accurate assessment to be made of the position of localized radioactivity in the testbed wall.